Inter-Rater Reliability among Dentists for Assessment of Angle of Impacted Third Molars on Orthopantomograms - Mahnoor Tariq, Muhammad Haseeb, Tehreem Khalid, Asma Shakoor, Hina Zafar Raja, Hira Butt, Maria Jabbar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the inter-rater reliability of dentists from various specialties regarding the observation and interpretation of angle of impacted third molars on the OPG. Methodology: A cross sectional comparative study was conducted in College of Dentistry, Sharif Medical and Dental College, Lahore after obtaining ethical clearance from ethical committee of Sharif Medical Research Centre (SMRC) in which dentists from four different specialties namely; Oral Pathology, Endodontics, Prosthodontics and Oral and Maxillofacial surgery were included as raters. The study was conducted from December 2020 to February 2021. A total of 21 Orthopantomograms were assigned to each rater for assessing the angle of the impacted third molar. The classification for angle of impaction used was Winter`s classification Results: The level of agreement regarding the angle of impacted third molars observed on the Orthopantomograms between rater 1 and rater 2 was very strong (κ=0.791,p≤0.001) but was moderate between rater 2 and rater 3 (κ=0.438, p≤0.001) and rater 2 and rater 4 (κ=0.577, p≤0.001) . Conclusion: The level of agreement regarding the angle of impacted third molars observed on the Orthopantomograms between rater 1 (oral pathologist) was very strong with rater 2 (Oral and Maxillofacial surgeon) while that of rater 2 with rater 3 (endodontist) and rater 4 (Prosthodontist) was moderate. Keywords: Inter-rater reliability, Orthopantomograms (OPG), impacted third molars, mesioangular, distoangular, vertical, horizontal